A Chance-Constrained Programming Approach to Cost-Volume-Profit Analysis. - Brockett, P.; Charnes, A.; Cooper, W. W.; Shin, Hong-Chul (The Accounting Review, 1984)
ABSTRACT: Earlier attempts to extend cost-volume-profit analyses to stochastic sales behavior are reinterpreted in terms of chance-constrained programming formulations to control for risks of failing to break even. The standard types of breakeven analyses usually employed as deterministic systems in accounting are shown also to apply in a surprisingly general manner to situations where risk or uncertainty in sales demands are present. Ways of extending such analyses to allow for new upper as well as lower limits on volume are developed and interpreted in detail. Suggestions and references are also supplied to indicate how such analyses can be extended further to provide contact with probabilistic programming (linear programming under uncertainty as well as stochastic linear programming and chance-constrained programming) approaches to planning and evaluation of portfolios of projects under combinations of liquidity and payback period constraints.